Pelatihan Intensif untuk Mengembangkan Keterampilan Dasar Laboratorium pada Mahasiswa Pendidikan Kimia - Rahmi, Ayu; Muliaman, Agus (LP2M Universitas Islam Ahmad Dahlan, 2025)
Basic laboratory skills are essential skills that Chemistry Education students must possess as future science educators. Accuracy in observation and precision in measurement are essential foundations for understanding chemical concepts through experimental activities. However, initial assessment results indicated that these skills were not yet optimally developed, especially among beginning students. Based on this condition, this community service activity was structured as intensive training focused on improving observation and measurement skills through workshops, demonstrations of laboratory equipment use, hands-on practice, and mentoring sessions. The program was attended by 26 students and lasted for three days. The evaluation of the activity showed improvements in the participants' procedural knowledge, technical skills, and scientific attitudes. This training proved effective in improving laboratory literacy and is recommended for ongoing implementation to strengthen students' competencies as future chemistry teachers.